3D analytical investigation on the overall pullout behavior of grouted anchorages in presence of shear failure of grout. (January 2020) - Wang, Yan-Jie; Wu, Zhi-Min; Zheng, Jian-Jun; Zhou, Xiang-Ming
Highlights: 3D analytical solution for the overall pullout behavior of grouted anchorages. Determination of local stress distribution and global load-displacement response. Validation by experimental and numerical results available in the literature. Identification of the difference between 1D solution and 3D solution. The proposed solution can be applied in other bonded structures with convenience. Abstract: Grouted anchorages have been extensively applied in practical projects like reinforcing steel anchors embedded into concrete or rock through cement grouting. The pullout behavior of the anchorages is generally a three-dimensional (3D) problem, whereas most existing analytical studies are based on a one-dimensional (1D) assumption such that the overall behavior of the anchorages has not been fully understood. In this paper, a 3D analytical solution is presented that is capable of predicting the overall pullout behavior of grouted anchorages in the presence of shear failure of grout, where the shear behavior of the grout is simulated by a bilinear shear stress-displacement relation. 3D closed-form solutions are deduced for the displacement field, the stress field and the load-displacement curve of both long and short anchorages for various loading phases. The analytical solution is validated by comparing the analytical results with the experimental and numerical results from the literature. The load-displacement characteristics of long and short anchorages are elaborated with the influence of the anchorage length on the load-displacement response evaluated. Comparative study is conducted to investigate the difference between 1D and 3D solutions on the global load-displacement response and the local shear stress distribution. The results show that there is no significant difference between 1D and 3D solutions in the case of very short anchorages. However, Poisson's effect plays an increasing role in the stress transfer as the anchorage length increases, leading to an increasing discrepancy between the two solutions, which demonstrates that neglecting Poisson's effect has an impact on the performance prediction of grouted anchorages. The present 3D analytical solution, with Poisson's effect taken into consideration compared to 1D solution, can be expected to be better capable of evaluating the overall pullout behavior of grouted anchorages, especially for long anchorages. While the present study is conducted with reference to grouted anchorages, the analytical solution remains applicable to similar bonded structures such as reinforced composites and cylindrical adhesive joints.